2013
DOI: 10.1186/1471-2458-13-239
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between children’s oral health-related behaviors and their caregiver’s sense of coherence

Abstract: BackgroundSense of coherence (SOC) is hypothesized to be an important psychological factor that enables people to cope with stressors and successfully maintain and improve health. Mother’s SOC has been shown to be an important psychological factor associated with oral health and oral health-related behaviors of adolescents and 11- to 12-year-old children. However, little is known about the relationship between the caregiver’s SOC and oral health-related behaviors of the preschool children. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 24 publications
4
57
0
2
Order By: Relevance
“…In this study, the caregiver’s social support was not significantly associated with a child’s frequency of sugary snack intake. The frequency of sugary snack intake by children was predominantly related to the caregiver’s frequency of sugary snack intake and other factors, which was also shown in our previous study [16, 22]. In addition, these findings revealed that a child’s sugary snack intake habits are influenced by his/her caregiver’s sugary snack intake habits.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the caregiver’s social support was not significantly associated with a child’s frequency of sugary snack intake. The frequency of sugary snack intake by children was predominantly related to the caregiver’s frequency of sugary snack intake and other factors, which was also shown in our previous study [16, 22]. In addition, these findings revealed that a child’s sugary snack intake habits are influenced by his/her caregiver’s sugary snack intake habits.…”
Section: Discussionsupporting
confidence: 85%
“…Most researchers also believe that oral health knowledge and parents’ attitudes mostly determine and promote children’s oral health behaviour. [1–3]…”
Section: Introductionmentioning
confidence: 99%
“…Oral health promotion is very important in order to insure the application of primary prevention methods such as daily toothbrushing at least twice a day, daily use of dental floss and visiting a dentist regularly to prevent and detect oral diseases in a early stage. Oral health education is the first step in the prevention of oral diseases, in order to decrease socio-demographic differences and to give equal opportunities of oral health, promoting the measures necessary for the improvement of quality-of-life among the population (Qiu et al, 2013;Yiu and King, 2011;Okullo et al, 2004;Pereira, 2003;Honkala et al, 2001).…”
Section: Introductionmentioning
confidence: 99%